EvalMSA: A Program to Evaluate Multiple Sequence Alignments and Detect Outliers. (January 2016) - Chiner-Oms, Alvaro; González-Candelas, Fernando
We present EvalMSA, a software tool for evaluating and detecting outliers in multiple sequence alignments (MSAs). This tool allows the identification of divergent sequences in MSAs by scoring the contribution of each row in the alignment to its quality using a sum-of-pair-based method and additional analyses. Our main goal is to provide users with objective data in order to take informed decisions about the relevance and/or pertinence of including/retaining a particular sequence in an MSA. EvalMSA is written in standard Perl and also uses some routines from the statistical language R. Therefore, it is necessary to install the R-base package in order to get full functionality. Binary packages are freely available fromhttps://sourceforge.net/projects/evalmsa/ for Linux and Windows.